The Availability and Utility of Services to Address Risk Factors for Recidivism Among Justice-Involved Veterans - Blonigen, Daniel M. (Criminal justice policy review, 2017)
The availability and utility of services to address recidivism risk factors among justice-involved veterans is unknown. We explored these issues through qualitative interviews with 63 Specialists from the Department of Veterans Affairs’ (VA) Veterans Justice Programs. To guide the interviews, we utilized the risk-need-responsivity (RNR) model of offender rehabilitation. Specialists reported that justice-involved veterans generally have access to services to address most RNR-based risk factors (substance abuse, lack of positive school/work involvement, family/marital dysfunction, lack of prosocial activities/interests), but have less access to services targeting risk factors of antisocial tendencies and associates and empirically based treatments for recidivism in VA. Peer-based services, motivational interviewing/cognitive-behavioral therapy, and Veterans Treatment Courts were perceived as useful to address multiple risk factors. These findings highlight potential gaps in provision of evidence-based care to address recidivism among justice-involved veterans, as well as promising policy-based solutions that may have widespread impact on reducing recidivism in this population.